Дослідження аналгетичної активності похідних 4-R-3-(морфолінометилен)-1,2,4-триазол-5-тіолу - Капелянович, Є. В.; Щербина, Роман Олександрович; Пругло, Євген Сергійович; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Kapelyanovich, E. V.; Shcherbyna, R. O.; Pruglo, E. S.; Panasenko, O. I.; Knysh, Ye. H. (My University, 2014)
Біль – це своєрідне відчуття, що виникає внаслідок сильних подразнень нервової системи. Больові подразнення сприймаються периферійними нервовими рецепторами і передаються по нервовим провідникам до головного мозку [1]. Метою наших досліджень було вивчення аналгетичних властивостей низки похідних 4-R-3-(морфолінометилен)-1,2,4-триазол-5-тіолу та встановлення деяких закономірностей залежності фармакологічної активності від хімічної структури синтезованих речовин. Pain is a protective reaction of the organism, which is the first sign of illness or signal of danger. Existing drugs for pain reducing exhibits a series of side effects. However, with an analgesic effect, most of these preparations displays lot of side effects. Thus, the searching for new highly effective and safe drug with pronounced analgesic activity is an actual problem of modern medicine and pharmacy. The purpose of our studies was to investigate the analgesic properties of some derivatives of 4-R-3- (morpholinomethylene)-1,2,4-triazole-5-thioles and detection of some regularities according to pharmacological activity and the chemical structure of synthesized compounds. For studying the analgesic effect of new derivatives of 1,2,4-triazole, and determine the effect of the central component in the nociceptive system the model of thermal limbs stimulation («hot plate») was used. The study has found of that most from tested compounds under the experimental conditions reduced the pain threshold in laboratory animals. However, the replacement of methyl substituent at N1 atom of nitrogen in molecule 3-(morpholinomethylene)-4-methyl-1,2,4-triazole-5-thiol (PKR-125) for phenyl substituent (PKR- 123) leads to a slight analgesic activity. It has been established, that the appearance of carboxylic group in the molecule reduces the analgesic effect of some synthesized compounds.
The analgesic activity research for the derivatives of 4-R-3-(morpholinomethylene)-1,2,4-triazole-5-thioles
Keywords: похідні 1,2,4-триазолу; аналгетична активність; «структура–дія»; derivatives of 1,2,4-triazole; analgesic activity; «structure–action»